2021
DOI: 10.3390/biom11030380
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAs and microRNAs as Essential Regulators of Stemness in Breast Cancer Stem Cells

Abstract: Breast cancer is an aggressive disease with a high incidence in women worldwide. Two decades ago, a controversial hypothesis was proposed that cancer arises from a subpopulation of “tumor initiating cells” or “cancer stem cells-like” (CSC). Today, CSC are defined as small subset of somatic cancer cells within a tumor with self-renewal properties driven by the aberrant expression of genes involved in the maintenance of a stemness-like phenotype. The understanding of the underlying cellular and molecular mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 165 publications
(149 reference statements)
0
13
0
Order By: Relevance
“…In the field of regenerative medicine, direct conversion has advantages in situ and in the generation of clinically relevant cells, including hard-to-achieve cells, from easily obtained cells such as fibroblasts [37,38]. The viral carrier transport efficiency of gene delivery can be high, depending on the type of vector used [15,27]; however, the risk of integration of viral DNA into the host genome raises potential safety issues for potential therapeutics and poses concerns like inefficient/unpredictable reprogramming outcomes, genomic integration, and unwarranted immune responses and toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of regenerative medicine, direct conversion has advantages in situ and in the generation of clinically relevant cells, including hard-to-achieve cells, from easily obtained cells such as fibroblasts [37,38]. The viral carrier transport efficiency of gene delivery can be high, depending on the type of vector used [15,27]; however, the risk of integration of viral DNA into the host genome raises potential safety issues for potential therapeutics and poses concerns like inefficient/unpredictable reprogramming outcomes, genomic integration, and unwarranted immune responses and toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…More attention has been paid to molecular mechanisms that play a key role in the development of HCC. It has been observed that many cell signaling pathways are essential in regulating critical cell processes, such as cell proliferation, cell cycle progression, and apoptosis [ 41 – 43 ]. As a ceRNA, LncRNA also participates in HCC cell proliferation, epithelial to mesenchymal transition (EMT), invasion and metastasis by regulating signaling pathways in HCC, such as nuclear factor κB (NF-kB) pathway, phosphatidylinositol 3′-kinase(PI3K)-Akt signaling pathway, Wnt/β-catenin pathway, TGF-β pathway, and Janus kinase signal transducer and activator of transcription (JAK/STAT) pathway, which are very important in the process of carcinogenesis (Fig.…”
Section: The Lncrna-mediated Cerna Network (Cernets) Functions By Modulating Signaling Pathways In Hccmentioning
confidence: 99%
“…There is a growing list of miRNA genes abnormally methylated in cancer, resulting in dysfunction in normal biological processes and carcinogenesis [ 179 ]. There are two categories for cancer-associated miRNAs: the oncogenic miRNAs (oncomiRs) are usually highly expressed, and they contribute to cancer development and progression and could be useful for diagnosis, prognosis and treatment [ 69 , 70 , 182 ], and the tumor-suppressive miRNAs (miRsupps), which inhibit tumorigenesis by regulating cell proliferation, apoptosis, invasion, metastasis and therapeutic resistance in BCSCs [ 25 , 183 ] ( Figure 2 ). For example, miR-31 is overexpressed in breast cancer and is directly activated by the NF-κB signaling pathway.…”
Section: Epigenetic Regulation In Breast Cancer and Bcscsmentioning
confidence: 99%
“…In addition to miRNAs, lncRNAs (200 nucleotides) have emerged as new players in stem cell signaling through multiple mechanisms, mainly via transcriptional, post-transcriptional and epigenetic regulation of genes and proteins, and both play pivotal roles in tumorigenesis, pluripotency, apoptosis, chemoresistance, angiogenesis, self-renewal and metastasis in BCSC subpopulations [ 183 , 196 , 197 ]. Unlike miRNAs and mRNAs, lncRNAs have low expression in breast [ 198 ].…”
Section: Epigenetic Regulation In Breast Cancer and Bcscsmentioning
confidence: 99%
See 1 more Smart Citation